Thermal Energy Estimation by In-situ Combustion in An Abandoned Oil Well - Ansari Maryam; Ghufran Alam (Universitas Islam Riau (UIR) Press, 2021)
A downside of producing oil is that it can never be fully recovered. After the end of a well's life span, the residual oil remaining in the reservoir on average can be over 30%. This residual oil can be extracted using enhanced oil recovery techniques, one of which combusts the oil in the formation where the average reservoir temperature can increase to 400⁰C for light oil and over 600⁰C for heavy oils. This method can become a significant catalyst in solving Pakistan's energy need and increasing power production. This paper aims to estimate the thermal energy production by combusting this residual oil using in-situ combustion by air injection technique. The study deals with the well Kahi-01 located in the upper Indus basin having three formations. The main target is the Hangu formation and its three reservoir blocks. This formation is characterized by its high residual oil percentage of 76-85% at depths of about 1691-1741 meters. The results show that the highest thermal energy output among the three reservoirs was 34.6e6 Megajoules. The highest power output from the binary plant was 38.5e4 Kilowatt hour.